Essay of Different Proportion of Protein on Growth of juvenile Distichodus antonii schilthius 1891.l. In vivo in Kisangani (D. R. Congo.) - Munganga Kabate Serge; Osombause Sango Joël; Kalala Gaëtan; Ngalya Benga Nathalie; Monsengo Mbabruki Franco; Ebwa Joël; Serkali Maliba (Britain International for Academic Research (BIAR) Publisher, 2022)
The present work was carried out in 201 at Facultural Institute of Agronomic Science of Yangambi in the province of Tshopo (RDC) and focuses on the Essay of different proportion of protein on growth of juvenile Distichodus antonii schilthius 1891.l. In vivo in Kisangani (D. R. Congo.) The objective pursued by this work was of study the performance of growth of juvenile of Distichodus antonii schilthius vivo in. Methodology and results: It resulted from the study that Distichodus antonii has doubled weight during all the experience. According to the t test of STUDENT calculated between the gain of body mass of fish fed with the food R1 continent 300% of protein and the R2 continent 25 % of protein showed a non significant difference (P<0,05). The SGR (Specific Growth Rate ‘‘SGR’’) appeared meaningfully and significantly correlated to the fed. The results of mortality rate during this experience did not seem being correlated to the different diet but rather to the manipulation of fish and other experimental protocols artefacts. The protein content of the carcasses of Distichodus varied of 117, 40% for the food R1 and 135, 84% for the food R2. The diet R2 appeared performing compared to the diet R1 according to body protein gain by unit of consumed protein and for the weight gain by unit of consumed protein by Distichodus antonii.